(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2016)
The collection of five articles in this themed issue of the KEMANUSIAAN the Asian Journal of Humanities (KAJH) presents philosophical research revolving around the theme of solidarity. How to think this theme? We can understand it as referring to relations of mutuality. Now the two terms "relation" and "mutuality" already invoke and cluster together a complex network of concepts, logics, histories and etymologies, each requiring further theoretical, maybe rigorous, meditation. What happens when the terms are combined together? What is at stake and what is being questioned? What logos is being solidified and what aporias, in turn, leak out?